FAKTOR-FAKTOR YANG BERPENGARUH PADA PROFITABILITAS PERUSAHAAN - HANSELA, JOLISA; HENDRA, HENDRA (E-Jurnal Manajemen Trisakti School of Management (TSM), 2024)
This study aims to analyze and determine the influence of Tangible Assets, Company Size, Sales Growth, Liquidity, and Leverage on Profitability. The research object used is food and beverage companies listed on the Indonesia Stock Exchange from 2016-2022. This study uses secondary data and the sampel used is food and beverages subsector companies listed on the Indonesia Stock Exchange from 2016-2022. The research method used is purposive sampling and there are 16 companies that meet the research criteria out of a total of 41 companies, resulting in a total sample of 112. The data were analyzed using descriptive statistics and regression panel with a REM model to testing all hypothesis. The research results show that Tangible Assets, Company Size, and Leverage have a negative effect on profitability. Tangible assets and size have a negative effect to profitability because more assets means more cash needed, and will reduce profitabillity of company. Leverage also has a negative effect because more leverage means more interest expense, and it will reduce the company profitability. Meanwhile, Sales Growth and Liquidity do not affect profitability.